INVESTIGATING ATHEISTIC TENDENCIES AND RELIGIOUS ORIENTATION AMONG PAKISTANI YOUTH: A COMPREHENSIVE SURVEY STUDY (Contemporary Journal of Social Science Review, 2025)
In recent years, Pakistani youth have exhibited notable shifts in their religious orientations amid increasing exposure to globalization, digital media, and modern education. This study explores the rise of atheistic trends and changing patterns of religious affiliation among young people in Pakistan, aiming to understand the social and intellectual factors driving these transformations. The central research question asks: What factors contribute to the emergence of atheistic or secular tendencies among Pakistani youth, and how do these trends relate to their religious affiliation and practices?Employing a survey-based methodology, data were collected from university students across various academic fields to assess their beliefs, practices, and attitudes toward religion. The findings reveal that while most respondents still identify as religious, a growing minority express doubt, selective religiosity, or disengagement from traditional practices. Education, peer influence, and social media emerged as key factors shaping these views. Although atheistic tendencies remain limited, their increasing visibility highlights a gradual transformation in belief systems among Pakistani youth. The study underscores the need for meaningful dialogue and educational efforts to address the intellectual and spiritual concerns of the younger generation.